2019
DOI: 10.5114/fn.2019.89857
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone: from modelling to implication in Parkinson’s disease

Abstract: Rotenone ([2R-(2α,6aα,12aα)]-1,2,12,12a-tetrahydro-8,9-dimethoxy-2-(1-methylethenyl)-[1]benzopyran[3,4-b]furo [2,3-h][1]benzopyran-6(6aH)-one) is a naturally occurring compound derived from the roots and stems of Derris, Tephrosia, Lonchocarpus and Mundulea plant species. Since its discovery at the end of the 19 th century, rotenone has been widely used as a pesticide for controlling insects, ticks and lice, and as a piscicide for management of nuisance fish in lakes and reservoirs. In 2000, Betarbet et al. re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 72 publications
1
54
0
1
Order By: Relevance
“…Dieldrin, an organochlorine pesticide, causes neurotoxic damage to the dopaminergic system [ 73 ]. Rotenone, an organophosphate, increases α-synuclein aggregation and inhibits mitochondrial complex I [ 74 ]. Various illicit substances can elevate ROS leading to neurotoxicity.…”
Section: Parkinson’smentioning
confidence: 99%
“…Dieldrin, an organochlorine pesticide, causes neurotoxic damage to the dopaminergic system [ 73 ]. Rotenone, an organophosphate, increases α-synuclein aggregation and inhibits mitochondrial complex I [ 74 ]. Various illicit substances can elevate ROS leading to neurotoxicity.…”
Section: Parkinson’smentioning
confidence: 99%
“…A bidirectional interaction between aSyn aggregation and mitochondrial dysfunction has been implicated in PD pathogenesis. In particular, increased levels of aSyn can lead to mitochondrial dysfunction [ 239 , 240 , 241 , 242 , 243 , 244 ], whereas, conversely, impairment of mitochondrial activity may accelerate aSyn pathology [ 245 , 246 , 247 , 248 ]; however, the precise underlying mechanisms remain to be elucidated. Both WT and mutant aSyn have been shown to interact with mitochondrial elements, altering both mitochondria morphology and function.…”
Section: Alpha-synuclein In Neurons: a Multifaceted Proteinmentioning
confidence: 99%
“…Nonetheless, there is evidence suggesting an impairment of mitochondrial function upstream of aSyn pathology. Experiments using the pesticides rotenone and paraquat have shown that dysregulation of mitochondrial function leads to nigrostriatal dopaminergic loss and formation of LB-like inclusions, positively stained with anti-aSyn antibodies and thioflavine S, thus resembling PD features [ 246 , 247 , 256 , 257 , 258 ]. Similarly, incubation of WT aSyn-overexpressing COS-7 cells with mitochondrial inhibitors resulted in the disappearance of the aSyn aggregates formed upon rotenone or oligomycin treatment [ 259 ].…”
Section: Alpha-synuclein In Neurons: a Multifaceted Proteinmentioning
confidence: 99%
“…Importantly, rotenone can easily pass through the blood–brain barrier, reaches the brain, and accumulates in mitochondria where it causes impairment of oxidative phosphorylation by inhibiting complex I and a decrease in energy production, which leads to neuronal death [ 3 ]. Evidence has shown that chronic treatment of animals with rotenone-induced selective degeneration of dopaminergic neurons and terminals in the substantia nigra pars compacta and striatum, respectively, motor deficits and postural imbalance reminiscent of Parkinson’s disease (PD) [ 4 , 5 , 6 , 7 ]. However, the neurotoxic effects of rotenone are not specific to the dopaminergic system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the intravenous injection of rotenone in rats caused a loss of striatal serotoninergic and dopaminergic fibers, nigral dopaminergic neurons, striatal cholinergic interneurons, cholinergic neurons in the pedunculopontine tegmental nucleus, and noradrenergic neurons in the locus coeruleus [ 8 ]. The chronic administration of rotenone produces not only motor deficits including rigidity, postural instability, akinesia/bradykinesia and tremor, but also extranigral signs and non-motor symptoms such as gastrointestinal dysfunction, hyposmia, sleep disturbance, circadian dysfunction, cognitive impairment, anxiety, and depression [ 6 , 7 , 9 ]. However, there is no study to examine the effects of rotenone on conditioned taste aversion memory.…”
Section: Introductionmentioning
confidence: 99%